Admission Diffusion-Weighted Imaging Lesion Volume in Patients With Large Vessel Occlusion Stroke and Alberta Stroke Program Early CT Score of ≥6 Points: Serial Computed Tomography-Magnetic Resonance Imaging Collateral Measurements. Issue 11 (November 2019) - Yu, Inwu; Bang, Oh Young; Chung, Jong-Won; Kim, Yoon-Chul; Choi, Eun-Hyeok; Seo, Woo-Keun; Kim, Gyeong-Moon; Menon, Bijoy K.; Demchuk, Andrew M.; Goyal, Mayank; Hill, Michael D.
Abstract : Background and Purpose—: We hypothesized that the pial collateral status at the time of presentation could predict the infarct size on magnetic resonance imaging in patients with similar degrees of early ischemic changes on computed tomography. We tested the association between serial changes in collateral status and infarct volume defined on diffusion-weighted imaging (DWI) in patients with large vessel occlusion and small core. Methods—: Consecutive patients who were candidates for endovascular treatment (Alberta Stroke Program Early CT Score [ASPECTS] of ≥6 points) and who underwent both pretreatment multiphasic computed tomography angiography (mCTA) and multimodal magnetic resonance imaging were enrolled. The baseline early ischemic changes and collateral status were determined using both mCTA and magnetic resonance imaging–based collateral maps. Multivariable linear regression was used to evaluate adjusted estimates of the effect of collateral status on predicting MR DWI lesion volume before endovascular treatment. Results—: Of 65 patients (39 men; median age, 76 years; median ASPECTS, 8 points [range, 6–10]), 10 (15.4%), 8 (12.3%), and 47 (72.3%) presented poor, intermediate, and good collaterals on mCTA, respectively. After adjusting for the initial stroke severity, ASPECTS, time to DWI, and mismatch volume, the mCTA collateral grade was the only factor independently associated with the DWI lesion volume (β=−35.657, SE mean=3.539; P <0.0001). An excellent correlation between the mCTA- and magnetic resonance imaging-based collateral grades was observed (matching grade seen in 92.3%), suggesting a collateral status persistence during the hyperacute stroke phase. Conclusions—: The mCTA assessed collateral adequacy is the sole predictor of eventual DWI lesion volume before endovascular treatment. The added value of collateral assessment in early ischemic changes and large vessel occlusion for decision-making regarding more aggressive revascularizations requires further evaluation. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03234634 and NCT02668627. Abstract : Supplemental Digital Content is available in the text.